Differences in Classroom Management Approaches across Teacher Demographic Variables: An ANOVA Study of Ethiopian Middle School EFL Teachers - Tsegaye Mitiku Zewdie; Seime Kebede (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study investigated whether English as a Foreign Language (EFL) teachers’ instructional management (IM) and behavior management (BM) approaches vary according to gender, teaching experience, and academic qualification in Ethiopian middle schools. A quantitative cross-sectional survey design was employed. Data were collected from 42 EFL teachers using a structured classroom management questionnaire comprising instructional and behavior management subscales. Internal consistency reliability was acceptable (α = .78 for IM; α = .78 for BM). One-way analysis of variance (ANOVA) was conducted to examine group differences, and effect sizes (η²) were calculated to assess practical significance. The findings revealed no statistically significant differences in instructional or behavior management across gender, experience, or qualification groups (p > .05). Effect sizes were small or negligible (η² ranging from .001 to .06), indicating that demographic variables accounted for minimal variance in classroom management practices. These results suggest that classroom management approaches among middle school EFL teachers are relatively stable across demographic categories. Institutional norms, shared professional training, and contextual factors may exert a stronger influence than individual demographic characteristics. The findings have implications for teacher professional development and educational policy design.